PENGARUH METODE PEMBELAJARAN DAN SIKAP BELAJAR SISWA TERHADAP NILAI AKADEMIK PADA SISWA SLTP NEGERI DI JAKARTA SELATAN - Eka Septiani (Universitas Nasional, 2016)
ABSTRACT The title of research is The Effect of Teaching Methods and Learning Attitude of Academic Grades in Junior High School Students in South Jakartat. The aims to determine (a) the effect of Indonesian method of learning the value of a student's academi. The aim of this research was to determine the effect of Indonesian learning method to academic grades of student (b) knowing the influence of learning attitude to academic grades of student (c) knowing the influence of Indonesian learning method and learning attitude to determine the effect of academic grades of student. The method used is a survey method. The sample size of 60 eighth grade student of SLTPN 41 and SLTPN 107, selected using simple random sampling technique. The data collection was done by using observation and using questionnaire. Analysis of the data by using is ANOVA dua jalur. The research result shows: 1) There is a significant direct effect of jigsaw learning method withconvensional learning method to Indonesian academic grades of student, retrieved price Fhitung (56,517) > Ftabel (2,77) at a significant level 5%. 2)There is a significant direct effect of high learning attitude withlow learning attitudeto Indonesian academic grades of student, retrieved price Fhitung (18,056) > Ftabel (2,77) at significantlevel 5%. 3) There is a significant direct effect of learning methodand learning attitude students toIndonesian academic grades of student, retrieved price Fhitung (5,235) > Ftabel (2,77) at significant level 5%. This research resultis useful for improvement Indonesian academic grades of student. Keyword: Indonesian learning method , learning attitude, and Indonesian academic grades of student.